Pengaruh Game “Sakura School Simulator” Terhadap Perkembangan Sosial Anak Usia Dini - Muhammad Raihan Nafis Suwarna; Idat Muqodas; Finita Dewi (Journal on Education, 2023)
The digital era is a time when information is more easily gained using the intermediary of digital technology. In this digital era there is something called online games. The purpose of this research is to find out whether the game "sakura school simulator" which is currently rife among early childhood has an impact on the child's social development.This type of research uses qualitative research with a case study research approach. The data collection techniques used by researchers are "semi-structured" interviews and "participant" observation, the sample of this study will research 1 child aged 5-6 years from a family with the characteristics of the mother as a housewife. The results of observation research and interviews conducted with the mother resulted in that playing the game has a positive and negative influence on children's social development. the influence of the game can have a positive and negative impact depending on the parenting carried out by parents and the environment.